ANALYZING STUDENTS’ SPEAKING ACTIVITIES IN TEACHING LEARNING PROCESS USING STAD METHOD - Osi Havis Melian; Mela Rosa Solihat (PROJECT (Professional Journal of English Education), 2019)
Speaking is one of the most important skills in English where the speakers can express opinion, ideas, responses, information. Speaking is a productive skill that can be done spontaneously or directly given attention about the accuracy of the content of conversation and fluency when speaking. Usually, students are planning first before they are speaking which is expected to be able to improve the smoothness and accuracy about what they will say. the researcher should  provide methode  that  make students  interested  to  learn speaking and can help their progress in speaking ability. Cooperative learning is a term of a general set of learning that is designed to enhance cooperation between students in learning. In cooperative learning, students work in pairs, to maximize their own and other learning. STAD (Students team achievement division) is one of the various technique in cooperative learning, which make promote collaboration and self-regulating learning ability. The reason why the researcher selection of STAD is good interaction among students, improve positive attitude towards subject, better self-esteem increased interpersonal skills. The teacher presents a lesson, and then students work within their teams to make sure that all team members have mastered the lesson. Finally, all students take individual quizzes on the material, at which time they may not help one another.